Effect of oxygen impurities in semipolar III‐nitride light emitting diodes. Issue 1 (19th September 2016) - Römer, Friedhard; Witzigmann, Bernd
Abstract: We investigate the effect of oxygen impurities on the internal quantum efficiency of semipolar III‐nitride light emitting diodes (LED) structures grown along the ( 20 2 ‾ 1 ) direction by means of carrier transport simulations. For the model calculations, realistic doping and impurity profiles obtained by secondary ion mass spectroscopy are used. We discuss the impact of the oxygen impurity density on the operation of the LED and the interaction of the donor‐type oxygen impurities with the acceptor doping. It is shown that up to a certain oxygen concentration, no major degradation of the LED efficiency occurs and that with increasing oxygen impurity density the LED efficiency becomes more sensitive to variations of the acceptor doping profile. The independent variation of the oxygen concentration revealed that oxygen impurities are most critical in the electron blocking layer and the p‐side barrier.